2014
DOI: 10.3390/nu6083169
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Intake in Italian Infants and Toddlers from North and South Italy: The Nutrintake 636 Study

Abstract: We performed a cross-sectional study to compare the intake of energy, macronutrients, fiber, sodium and iron and the anthropometric status of infants and toddlers living in North (Milano) and South Italy (Catania). Nutrient intake was evaluated using a 7-day weighed food record. Out of 400 planned children aged 6 to 36 months, 390 (98%) were recruited, 189 in Milano and 201 in Catania. The mean (standard deviation) age was 17 (9) months in Milano and 17 (10) months in Catania. Anthropometry, energy intake and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
28
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 29 publications
(45 reference statements)
7
28
1
Order By: Relevance
“…In addition, research indicates that eating salty foods in the first two years of life can influence sensitivity to and subsequent preference for these foods later in life (Ahluwalia, Herrick, Paulose- Ram, & Johnson, 2014) (Stein, Cowart, & Beauchamp, 2012). Consistent with US results, four international studies found that on average, children consume amounts of sodium higher than recommended limits (Grimes, Campbell, Riddell, & Nowson, 2011) (Zuccotti et al, 2014) (Marrero, He, Whincup, & MacGregor, 2014) (Campbell et al, 2014). …”
Section: Introductionsupporting
confidence: 67%
“…In addition, research indicates that eating salty foods in the first two years of life can influence sensitivity to and subsequent preference for these foods later in life (Ahluwalia, Herrick, Paulose- Ram, & Johnson, 2014) (Stein, Cowart, & Beauchamp, 2012). Consistent with US results, four international studies found that on average, children consume amounts of sodium higher than recommended limits (Grimes, Campbell, Riddell, & Nowson, 2011) (Zuccotti et al, 2014) (Marrero, He, Whincup, & MacGregor, 2014) (Campbell et al, 2014). …”
Section: Introductionsupporting
confidence: 67%
“…Similar results have been found in other European countries for this age group. Huysentruyt et al found that all the Belgium children between 6 to 36 months (n = 500) had a protein intake above the recommended dietary intakes and for 156 children (33.5%), were above the UL of 15% of total energy intake that was proposed by ESPGHAN [54,55] The NUTRINTAKE cross-sectional study (n = 390) in Italian children aged 6 months to 3 years found a high intake of proteins, simple carbohydrates, saturated fats and sodium compared with the Italian recommended dietary allowances [56].…”
Section: Nutrient Profile and Distributionmentioning
confidence: 92%
“…Instead, the risk categories of our tool were compared to an exhaustive nutritional assessment, obtained from a 3DWFR that reflected the detailed food consumption of the toddlers involved in the study. Despite TDQ being useful in the identification of dietary risk, described as ‘any appropriate dietary pattern that may impair health’, NutricheQ focuses on some specific aspects of dietary imbalances, primarily those dietary patterns and habits that might lead to poor iron and vitamin D intake, a matter of serious concern for Italian toddlers, as described in the Nutrintake 636 Study ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in keeping with recent evidence from the Nutrintake 636 Study, an epidemiological study investigating the nutritional habits of 636 Italian toddlers aged <12 months using a 7-day weighed food record. Despite having normal anthropometry and energy intake, toddlers had a high intake of proteins, sugars, saturated fatty acids, and sodium; and a low intake of iron and fibre compared to Italian DRVs ( 1 ). Recently, the inadequate intake of fruits and vegetables has been reported also in Dutch toddlers ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation